MEMPROBLEMATISASI PERAN KOTA DALAM TATA KELOLA LINGKUNGAN GLOBAL - Gema Ramadhan Bastari; Lathiefah Widuri Retyaningtyas (Review of International Relations, 2019)
This paper will discuss about problems surrounding discourse on the role of local government or ‘city’ in global environmental governance. Many scholars, such as Acuto (2013), Betsill & Bulkeley (2010) and Fraser (2014) have argued that city might be the missing actor that global environmental governance needs to make it work. However, this paper believes that the argument is riddled with fallacy, most notably with the way they did not take into account the existence of growth-based development ideology that can prevent local government from truly preserving the environment. This paper argues that city is not the panacea that will solve all environmental problems since it favors utilitarianism approach over deep ecology. However, this paper acknowledges that city could be the new norm entrepreneur that can strengthen international norm on environmental preservation.Keyword: City, Environment, Norm, Utilitarianism